The Effect of Grammar Translation Method on Students’ Writing Narrative Text Ability - Linda Efrina Nasution (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
The objective of this research was to find out the effect of grammar translation method on students’ writing narrative text ability at the tenth grade students of MAS Al – Hakimiyah Paringgonan. The research design of this research is experimental research by using “one group pre –test and post test design. Where the writer did an experiment in a single group only. The population of this research are students from tenth grade which is consist of 159 students and get 39 students as sample which selected by using cluster sampling technique. The test is used as the instrument of this research, after collecting the data, it was analyzed using the t.test formula. The data analysis found that the mean or average of students' scores after the treatment is 82.17. Using the statistical analysis, the researchers get to 25.70, where the value of t.table is 2.024. It means that the value of t observed is greater than that of the t table (to = 25.70 > t table = 2.024). The alternative hypothesis of this research is accepted, After the calculation it is found that the gain score is 0.7. the score of 0.7 can be classified as middle effect, means that grammar translation method effectively affect students’ ability in writing narrative text.